Molecular structures and biological evaluation of 2-chloro-3-(n-alkylamino)-1,4-napthoquinone derivatives as potent antifungal agents - Pawar, Omkar; Patekar, Ashwini; Khan, Ayesha A.; Kathawate, Laxmi; Haram, Santosh K.; Markad, Ganesh; Puranik, Vedavati G.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Derivatives of 2-chloro-3-(n-alkylamino)-1,4-naphthoquinone (1-alkyl: methyl; L-1, ethyl; L-2, propyl; L-3 and butyl; L-4) have been synthesized and characterized by elemental analysis, FT-IR, H-1 NMR, UV-visible spectroscopy, LC-MS and single crystal X-ray diffraction studies. Antifungal activity of L-1 to L-4 has been evaluated against Candida tropicalis, Candida albicans and Cladosporium herbarum. The intramolecular hydrogen bonding affects the N-H vibrational frequency in L-2 (3273 cm(-1)). The single crystal X-ray structure reveal that L-1 and L-3 crystallizes in triclinic P-1, whereas L-2 crystallizes in orthorhombic Pca2(1), space group. An extensive intra and intermolecular hydrogen bonding interactions were observed in L-1 to L-3 which leads to molecular association. Intramolecular N-H center dot center dot center dot O hydrogen bonding were observed in L-1 to L-3. Moreover pi-pi stacking interactions were observed between the quinonoid rings of L-1 and L-3, however no such interactions were observed in L-2. An electrochemical study showed molecular association of L-1 to L-4 in DMSO solution. Compounds L-1 to L-4 were found to be potent antifungal agents against all the three strains, especially against C. tropicalis. Amongst these promising antifungal candidates, L-1 showed better activity compared to the clinically administered antifungal drug Amphotericin B and Nitrofurantoin with MIC = 1.25 mu g ml(-1) and MIC = 0.025 mu g ml(-1) respectively against C. albicans. Structure and activity relationship (SAR) study suggest a LogP value of similar to 2.0 and the cyclic voltammetry studies reveals additional chemical processes for L-1, which exhibits maximum activity against all fungal strains. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Antifungal activity; LogP; Naphthosemiquinone; pi-pi stacking

Reaction between lawsone and aminophenol derivatives: synthesis, characterization, molecular structures and antiproliferative activity - Kathawate, Laxmi; Joshi, Pranya V.; Dash, Tapan Kumar; Pal, Sanjima; Nikalje, Milind; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2014)
Reaction between two bioreductive reactants lawsone (2-hydroxy-1,4-napthoquinone) and derivatives 2-aminophenol without catalyst is reported. The reaction between lawsone and 4-chloro-2-aminophenol leads to formation of red colored major product 1A:[2-[(5-chloro-hydroxyphenyl)amino]naphthalene-1,4-dione] and fluorescent orange colored minor compound 1B:[10-chloro-benzo[alpha]phenoxazine-5-one]. Molecular structure of 1A and 1B were determined by single crystal X-ray diffraction. Two mechanisms were proposed to the formation of red 1A and 1B. `Ortho-para' tautomeric equilibrium was observed in DMSO-d(6) solution in 1A, which was revealed by H-1, C-13 NMR and LC-MS studies. Molecules of 1A formed dimers via N-H center dot center dot center dot O interaction and polymeric chain of dimers was formed by OH center dot center dot center dot O interactions. Cl center dot center dot center dot Cl interactions were observed between the polymeric chains of dimers in 1A. Molecules of 1B show Cl center dot center dot center dot N interaction. Antiproliferative properties is studied for 1A-5A compounds (obtained by the reaction of lawsone with 2-amino-4-methylpheno1;2A, 2-aminopheno1;3A, 3-aminophenol;4A and 4-aminophenol;5A) and evaluated against two cancer cell lines, THP1 (human monocytic leukemia cells) and COLO205 (colorectal adenocarcinoma) and one normal cell line, HEK293T (human embryonic kidney). The values of 50% inhibitory concentration (IC50) of compounds 1A-5A was determined using XTT assay. The cytotoxic effects of compounds 2A and 3A were observed against COLO205 and compounds 4A and 5A on THP1 were observed to be higher in comparison to their effect on HEK293T cell lines. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Aminophenol; Benzo[alpha]phenoxazine; Cl center dot center dot center dot N interactions; Lawsone; pi-pi stacking interaction

Synthesis, characterization and molecular structures of homologated analogs of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone - Salunke-Gawali, Sunita; Pawar, Omkar; Nikalje, Milind; Patil, Rishikesh; Weyhermueller, Thomas; Puranik, Vedavati G.; Konkimalla, V. Badireenath (Journal of Molecular Structure, 2014)
Four analogues of 2-bromo-3-(n-alkylamino)-1,4-napthoquinone (where n-alkyl is methyl in L-1Br, ethyl in L-2Br, propyl in L-3Br and butyl in L-4Br) are synthesized and characterized. A reaction mechanism is proposed for the formation of L-1 Br to L-4Br from the starting material 2,3-dibromo-1,4-naphthoquinone. The v(N-H) frequency in the FT-IR spectra is affected by the intramolecular hydrogen bonding in L-1Br to L-4Br and is observed similar to 3267 cm(-1) in L-2Br. A shift of similar to 25 cm(-1) is observed in the v(C-Br) frequency in all the compounds as compared to 2,3-dibromo-1,4-naphthoquinone (627 cm(-1)). A broad charge transfer band is observed between 400 and 600 nm in the UV-Vis spectra, which imparts red colour to all the compounds. Molecular structures of L-2Br and L-3Br were studied by single crystal X-ray diffraction studies. Molecules of L-2Br crystallize in Pca2(1), whereas the molecule L-3Br crystallizes in the P-1 space group. Molecules of L-2Br forms a polymeric chain through N-H...O interaction and forms beautiful butterfly like arrangement of molecules when viewed down the `a' axis. Ladder like polymeric chain of molecules is observed in L-3Br via C-H...O and N-H...O interactions. Every alternating neighbouring chains of L-3Br, show pi-pi stacking interactions between the quinonoid rings of the molecules, however this interaction is not observed in L-2Br. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: 2; 3-Dibromo-1; 4-naphthoquinone; Aminonaphthoquinone; hydrogen bonding; Michael addition; pi-pi stacking

Naphthoquinone based chemosensor 2-(2 `-aminoethylpyridine)-3-chloro-1,4-naphthoquinone: detection of metal ions, X-ray -crystal structures and DFT studies - Patil, Amit; Ware, Anuja P.; Bhand, Sujit; Chakravarty, Debamitra K.; Gonnade, Rajesh G.; Pingale, Subhash S.; Salunke-Gawali, Sunita (Journal of Molecular Structure, 2016)
Naphthoquinone based Chemosensor 2; 2-(2'-aminoethylpyridine)-3-chloro-1,4-napthoquinone have been synthesized and characterized. Chemosensor 2 crystallizes in the orthorhombic space group Pbcn and shows extensive intramolecular as well as intermolecular hydrogen bonding interactions. Each molecule of Chemosensor 2 showed interaction with five neighboring molecules via C-H center dot center dot center dot N, N-H center dot center dot center dot N, C-H center dot center dot center dot Cl and C-H center dot center dot center dot O interactions. Slipped pi-pi stacking interaction was observed in adjacent quinonoid and benzenoid rings. Chemosensor abilities of Chemosensor 2 ligand have been evaluated with metal ions viz. Cu2+, Ni2+, Zn2+, Co2+, Fe3+, Mn2+, Cr3+, Hg2+, La3+ and Cd2+ in methanol, methanol-water mixture and in presence of mild base triethylamine. Stoichiometry of Chemosensor 2 with metal ions such as Cu2+, Ni2+, Zn2+ and Co2+ ions was determined by Jobs method in methanol and were found as 1:1 for Cu2+ and 2:1 for Ni2+, Zn2+ Co2+. The variation in the metal ligand ratio is observed in aqueous media for Cu2+. Chemosensor 2 can be used selectively for naked eye detection of Cu2+ ions. The association constant obtained in methanol shows the trend Cu2+>Ni2+>Co2+. Cu2+ and two (Ni-1 and Ni-2) Ni2+ complexes were synthesized. Ni-2 complex showed coordination of Chemosensor 2 ligands was through pyridine nitrogen's only. The Chemosensor 2 and its deprotonated forms in methanol, water and triethylamine were also studied by TD-DFT studies. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Aminonaphthoquinone; Chemosensor; hydrogen bonding; Naphthoquinone; pi-pi stacking; TD-DFT